Use of stevia (Stevia rebaudiana Bertoni) in suckling and weaned pig diets - Watanasit, S. (Songklanakarin Journal of Science and Technology (SJST), 2003)
Four levels of stevia supplementation in the diet of suckling pigs with combination of two feeding methods in weaned pigs were studied. Twenty litters with nine piglets each were allocated to four groups and fed four dietary stevia supplementations (0, 0.2, 0.4 and 0.6%) from 7 days old to 21 days, weanling age. Two male weanlings of average weight of each litter were selected and alloted to one of two feeding methods, one male was fed basal diet 1 continuously while the other was fed by alternating basal diet 2 and basal diet 1 for 35 days of experiment, according to the split plot in randomized complete block design.The results showed that piglets fed with 0.2 and 0.4% stevia in suckling diets had double daily feed intake compared to those fed 0% stevia in the diet (12.36 vs 5.93 g/d), but this difference was not statistically significant (P>0.05). The daily feed intake and average daily gain decreased when suckling pigs were fed with 0.6% stevia in the diet. Continuous or alternating feeding had no effect (P>0.05) on feed intake and growth performance of weaned pigs (aged 21-56 days) fed with various levels of stevia supplementation in the diets. However, daily feed intake of weaned pigs fed with 0.4% stevia (748 g/d) was significantly (P<0.01) higher than that of pigs fed with 0, 0.2 and 0.6% stevia in the diets (617, 649 and 589 g/d, respectively). Average daily gain followed the same pattern (507 vs 419, 455 and 401 g/d, respectively, P<0.01). Moreover, although feed cost per gain of piglets fed with 0.2 and 0.4% stevia in the diets were higher, the income was higher than those fed with 0% stevia in the diet.